Maximal torque and power pedaling rate relationships for high level BMX riders in field tests - Debraux, P.; Vilizarova Manolova, A.; Soudain-Pineau, M.; Hourde, C.; Bertucci, W. (Journal of Science and Cycling, 2013)
The Bicycle Motocross race is an "all-out" sprint discipline with a race time not exceeding 40s. In high-level, the maximal power output during acceleration phase can be higher than 2000 W. The purpose of this study was to analyse the maximal torque- and power-pedaling rate relationships and anthropometric characteristics during 80m sprints. Seven elite riders performed three 80m sprints on a levelled ground. The maximal mechanical power output (PMAX), the mean pedaling rate (PRmean), the optimal pedaling rate (PROpt), the maximal theoretical pedaling rate (PR0), the maximal theoretical torque (T0), the time at 20m (t20) and the maximal velocity reached during 80m sprint (vMAX) were measured using PowerTap system and photoelectric cells. Moreover, the projected frontal area (Ap) was measured during the sprints by photographs. Significant correlations (P < 0.05) were observed between PMAX and vMAX (r = 0.99), vMAX and PMAX/Ap (r = 0.87), vMAX and T0 (r = 0.97), vMAX and PRmean (r = 0.98) and t20 and vMAX (r = -0.99). Moreover there was a significant difference (P < 0.01) between PRmean and PROpt with PRmean significantly greater than PROpt (158 ± 9 vs. 122 ± 18 rpm). The main results of this study showed that PMAX, T0, PRmean, Ap and t20 were significant determining factors of performance in 80m sprint. Furthermore, a lower value of PRmean could permit to reduce the difference between PRmean and PROpt in order to maximize the power output during the sprint.